Social change sans social conflicts: An exploration in the cultural terrain - Yadav, Sushma (2002)
The cultural identities have played a significant role in fostering social amity and fraternity over various stages of human development. Even in the present day this identity cuts across the political boundaries of countries. On the other hand regionalisms and cultural parochialisms have threatened the civic and social fabric. The article brings into focus the significance of cultural integration in warding off causes and effects of social tensions. The author emphasises the need of keeping intact cultural and moral values of our society at a time when the pace of social, political and economic changes have gathered unprecedented momentum. - Reproduced.
Keywords: Social conflicts